Broad‐range metalloprotease profiling in plants uncovers immunity provided by defence‐related metalloenzyme. Issue 3 (26th May 2022) - Morimoto, Kyoko; Krahn, Daniel; Kaschani, Farnusch; Hopkinson‐Woolley, Digby; Gee, Anna; Buscaill, Pierre; Mohammed, Shabaz; Sieber, Stephan A.; Cravatt, Benjamin F.; Schofield, Christopher J.; van der Hoorn, Renier A. L.
Summary: Plants encode > 100 metalloproteases representing > 19 different protein families. Tools to study this large and diverse class of proteases have not yet been introduced into plant research. We describe the use of hydroxamate‐based photoaffinity probes to explore plant proteomes for metalloproteases. We detected labelling of 23 metalloproteases in leaf extracts of the model plant Arabidopsis thaliana that belong to nine different metalloprotease families and localize to different subcellular compartments. The probes identified several chloroplastic FtsH proteases, vacuolar aspartyl aminopeptidase DAP1, peroxisomal metalloprotease PMX16, extracellular matrix metalloproteases and many cytosolic metalloproteases. We also identified nonproteolytic metallohydrolases involved in the release of auxin and in the urea cycle. Studies on tobacco plants ( Nicotiana benthamiana ) infected with the bacterial plant pathogen Pseudomonas syringae uncovered the induced labelling of PRp27, a secreted protein with implicated metalloprotease activity. PRp27 overexpression increases resistance, and PRp27 mutants lacking metal binding site are no longer labelled, but still show increased immunity. Collectively, these studies reveal the power of broad‐range metalloprotease profiling in plants using hydroxamate‐based probes.